IMPLEMENTATION OF KAHOOT APPLICATION TO IMPROVING OF INTEREST OF CIVIC EDUCATION LEARNING (EXPERIMENTAL RESEARCH IN CLASS XI OF SMA NEGERI 1 GARUT) - Yogga Mar Muhammad; Tetep (Institut Pendidikan Indonesia, 2018)
This research aims to determine the implementation of the kahoot application in increasing learning interest of Civic Education Learning, the achievement result of increased interest in learning Civic Education by using the kahoot application, and the achievement result of the effect the implementation of the kahoot application in increasing Civic Education learning interest. This study uses a quantitative research design with the experimental model, True Experimental with the Pretest-Posttest of Control Group Design conducted on students in class XI with a research technique using Random sampling. Techniques of Data collection were carried out by giving a pretest in one group that was given a treatment or what was called an experimental class. After that, students are given a final test and questionnaire at the end of the lesson. The results of the study in terms of cognitive aspects (learning interest) showed that the study class results had a gain normalized by 0.75 or 75%, with an average pretest of students at 60.5 and an average posttest score of 90.5. Based on the results of the processing of research data shows that there is a significant influence between the use of the kahoot application and increasing interest in PKn Subject, namely 54.6%.